Global Water Issues and Insights - R. Grafton, Quentin; Wyrwoll, Paul; White, Chris; Allendes, David (ANU Press, 2014)
This book brings together some of the world's leading water researchers with an especially written collection of chapters on: water economics; transboundary water; water and development; water and energy; and water concepts.